How has the Practice of Physical Activity Changed During the COVID-19 Quarantine? A Preliminary Survey - Raiola, Gaetano; Aliberti, Sara; Esposito, Giovanni; Altavilla, Gaetano; D'Isanto, Tiziana; D'Elia, Francesca (Physical Education Theory and Methodology, 2020)
Research purpose. The present study aims to examine the changes in physical activity levels during the lockdown due to COVID-19 in Italy. In particular, it aims to evaluate the impact of physical exercise on psychological health, how much the home environment influences the desire to train and what people think about Smart-fitness and sport in general. Materials and methods. A sample of 268 people from the province of Salerno participated in the study, with an average age of 26 years. To achieve the tasks set, the study relied on the following methods: analysis of scientific literature, formulation and administration of a questionnaire and data analysis through methods of mathematical statistics. A structured questionnaire was prepared, disseminated through social networks. To analyze the data, the Social Sciences Statistical Package (SPSS) and descriptive statistics were used to calculate the demographic variables. The factor analysis was also calculated to verify the characteristics of the sport considered important by the participants. Results. The results obtained made it possible to understand the main type of physical activity carried out during the quarantine (aerobic activity 35%, functional training 27%, anaerobic activity 19%), the time dedicated to each session (52.8% practice for 1 hour) and the weekly frequency of the same (42.9% practice physical activity continuously more than ¾ times a week). It was also understood the reasons that prompted the interviewees to train, the way they planned their session and the equipment used. Finally, it was shown that the majority of the sample (64.17%) knew smart fitness considering it an interesting activity, and the influence attributed to the home environment by a scale of values from 1 to 5. Furthermore, the factor analysis shows us the most relevant aspects wich respondents attributed to sport. More frequently, respondents place greater importance on being loyal and correct, on the contrary, lower values are attributed to the importance of earning money, and not to disappoint others. Conclusions. The study found that COVID-19 did not stop athletes, who quickly adapted to the new situation. The home environment has proved to be very influential on the desire to train, despite this, they hope to return to the gym as soon as possible.